2021
DOI: 10.3390/ma14123426
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Welding Speeds on the Morphology, Mechanical Properties, and Microstructure of 2205 DSS Welded Joint by K-TIG Welding

Abstract: In this paper, 8.0 mm thickness 2205 duplex stainless steel (DSS) workpieces were welded with a keyhole tungsten inert gas (K-TIG) welding system under different welding speeds. After welding, the morphologies of the welds under different welding speed conditions were compared and analyzed. The microstructure, two-phase ratio of austenite/ferrite, and grain boundary characteristics of the welded joints were studied, and the microhardness and tensile properties of the welded joints were tested. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…Likewise, there was no apparent relationship between nitrogen content and austenite formation with the arc energy for either Ar + 5% N 2 or Ar + 8% N 2 . Ar exhibited some weld metal nitrogen loss and a slight increase in ferrite fraction with higher arc energy, which aligns with previous studies [29,132,135].…”
Section: Travelling Arc Weldingsupporting
confidence: 92%
“…Likewise, there was no apparent relationship between nitrogen content and austenite formation with the arc energy for either Ar + 5% N 2 or Ar + 8% N 2 . Ar exhibited some weld metal nitrogen loss and a slight increase in ferrite fraction with higher arc energy, which aligns with previous studies [29,132,135].…”
Section: Travelling Arc Weldingsupporting
confidence: 92%
“…The formation of the "keyhole" also depends on the welding speed and a lack of penetration was also observed for a welding current of 530 A, when the welding speed was increased, thus decreasing the linear energy to 1.9 kJ/mm in the case of 10.8 mm plates [19]. If the thinner plates were welded, the higher welding speeds were acceptable (and the lower welding energies) [21]. In our research, when the welding current increased to 490 A, a complete penetration in the joint was reached with a correctly formed joint root, as shown in Figure 2, even though the linear energy was 2.18 kJ/mm; a value comparable to that for which there was a lack of fusion observed for lean duplex steel [19].…”
Section: Microstructures Of the Welded Jointsmentioning
confidence: 93%
“…Although this technology is very promising due to the efficiency of the welding process, it is still not widespread in industrial practice. First studies have shown its suitability for the welding of steel S32101 (lean duplex) [19][20][21]. Nevertheless, the implementation of this technology in industrial practice, especially for the welding of "difficult" steels such as duplex steels, requires a number of further studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the cooling stage after welding, the weld microstructure experiences the process of the phase transformation, from the high temperature ferrite phase to the austenite phase. However, due to the rapidity of cooling, the precipitation of the austenite phase is insufficient, resulting in the disproportion of ferrite and austenite in the weld [7] and thus the deterioration of the performance. Therefore, how to effectively control the ferrite/austenite phase ratio in the weld microstructure after welding, so as to ensure the stability of the mechanical properties of the weld joint, is a worthy problem with significant engineering value.…”
Section: Introductionmentioning
confidence: 99%